2013
DOI: 10.5037/jomr.2013.4102
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Deregulations in Head and Neck Squamous Cell Carcinomas

Abstract: ObjectivesHead and neck/oral cancer, predominantly head and neck squamous cell carcinoma (HNSCC), is the sixth most common cancer in the world. While substantial advances have been made to define the genomic alterations associated with head and neck/oral cancer, most studies are focused on protein coding genes. The aim of this article is to review the current literature on identified genomic aberrations of non-coding genes (e.g., microRNA) in head and neck/oral cancer (HNOC), and their contribution to the init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
76
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(78 citation statements)
references
References 162 publications
2
76
0
Order By: Relevance
“…In fact, hsa-miR-133a targets several oncogenes and is reported to be commonly down regulated in a number of other oral cancer studies [35][40]. Expression of both hsa-miR-31 and hsa-miR-31* was reported in some earlier study on cancer [41][42]. Study on OSCC cell line showed that exogenous delivery of pre-mir-31 , which boosts up quantity of mature hsa-miR-31 and hsa-miR-31* , enhanced OSCC oncogenicity [41][42].…”
Section: Discussionmentioning
confidence: 93%
“…In fact, hsa-miR-133a targets several oncogenes and is reported to be commonly down regulated in a number of other oral cancer studies [35][40]. Expression of both hsa-miR-31 and hsa-miR-31* was reported in some earlier study on cancer [41][42]. Study on OSCC cell line showed that exogenous delivery of pre-mir-31 , which boosts up quantity of mature hsa-miR-31 and hsa-miR-31* , enhanced OSCC oncogenicity [41][42].…”
Section: Discussionmentioning
confidence: 93%
“…As a consequence, deregulation in functioning or expression of miRNAs has been well-documented to result in a variety of human diseases, especially cancer, wherein miRNA themselves are known to function as oncogenes and tumor suppressors (Nelson and Weiss, 2008;Shiiba et al, 2010;Nohata et al, 2013). Several previous publications has substantiated the involvement of miRNAs in the pathogenesis of OSCC, and a compendium of miRNAs were shown to be differentially expressed (Chang et al, 2008;Chen et al, 2013). However, there has been limited research in OSCC on miRNAs that regulate or are regulated by TP53.…”
mentioning
confidence: 99%
“…Among the miRNAs correlated with carcinogenesis, miR193a-3p is one of the most important. Dysregulation of miR193a-3p has been reported in various types of cancer, such as NSCLC (29), prostate cancer (30), breast cancer (31), head and neck squamous cell carcinoma (32), colorectal cancer (33), myeloid leukemia (34), and Wilms tumor (35). The carcinogenic impact of miR-193a-3p has been attributed to its repression of c-Kit (34) and the PTEN/PI3K signaling pathway in acute myeloid leukemia (34); of KRAS and PLAU in colon cancer (36); of PLAU (37) and EGFR-driven cell cycle network proteins (38) in breast cancer; of ARHGAP19, CCND1, ERBB4, KRAS, and Mcl-1 in epithelial ovarian cancer (39); of PLAU in hepatocellular carcinoma (40); and of Mcl-1 in NSCLC (41).…”
mentioning
confidence: 99%